Selectivity Reversal during Thia-Michael Additions Using Tetrabutylammonium Hydroxide: Operationally Simple and Extremely High Turnover - Nicponski, Daniel R.; Marchi, Jennifer M. (Synthesis, 2014)
The use of tetrabutylammonium hydroxide as a novel and exceedingly efficient thia-Michael addition catalyst is herein described. This extremely simple methodology allows for the conjugate addition of a wide variety of mercaptan nucleophiles, and functions remarkably well with a very wide range of both classical and non-classical Michael acceptors. Contradistinctive to current literature reports, the use of this catalyst more efficiently promotes the addition of more basic thiols. This methodology is especially attractive and operationally simple, as it generally proceeds with only 1 mol% catalytic loading and without excess reagent, and the produced products typically require no purification.
Keywords: thia-Michael reaction; conjugate addition; catalysis; green chemistry; high turnover number; selectivity reversal